The Place of Pleasure in Neo-Aristotelian Ethics - Butler, Travis (American catholic philosophical quarterly, 2023)
Richard Kraut argues that Neo-Aristotelian ethics should include a commitment to "diluted hedonism," according to which the exercise of a developed life-capacity is good for S only if and partly because S enjoys it. I argue that the Neo-Aristotelian should reject diluted hedonism for two reasons: first, it compromises the generality and elegance of the initial developmentalist account; second, it leads to mistaken evaluations of some of the most important and ennobling capacities and activities in human life. Finally, I argue that a more plausible account of the place of pleasure in the good life derives from Aristotle’s discussion in book X of the Nicomachean Ethics: pleasure is a supervenient good that signifies the value of the underlying capacity and activity, but it is not a necessary condition for their goodness.